Symbolic Meanings in The Mammatua Ritual of Bugis Marriage Culture - Hasnani Siri; Musyarif Musyarif; Feby Adwiah Lestari; Muhammad Alwi (Warisan: Journal of History and Cultural Heritage, 2025)
The implementation of marriage in an area has its traditions and the Bugis tribe's marriage. Some customs are attached to the procession and have good meanings. The meaning of the wedding procession is often only known by traditional leaders or a group of people who are traditional observers. As a result, the older generation fails to transmit these customs effectively to the next generation. This research aims to explore the symbolic meaning of one of the Bugis tribe's wedding processions, which is called the Mammatua. The research method uses a descriptive approach with a qualitative research type. The authors collected the research data through observation, documentation, and interviews. We conducted observation and documentation directly at one of the Bugis tribe wedding processes in Baranti District, Sidrap Regency. Informants consisted of traditional leaders and local community members involved in the Mammatua procession at one of the weddings. The research information collected was then validated using symbolic validity with the involvement of anthropologists. The validated data was then analyzed using data reduction, presentation, and verification techniques. The study results show that the Mammatua is carried out after the wedding reception to ask for blessings from the bride and groom's parents. The procession features the exchange of lipa sabbe (silk sarongs) between families as a symbol of mutual respect and familial unity. In contrast, the offering of penne anreang (plates containing staple foods, ingredients, and traditional cakes) expresses the hope that the bride and groom will uphold the integrity of their household. These meanings emerge from symbolic interactions that the community has continuously expressed and practiced across generations, eventually becoming embedded beliefs that are actively preserved.